Novel Entry Pathway of Bovine Herpesvirus 1 and 5 - Wild, Peter (American Society for Microbiology, 1998)
Herpesviruses enter cells by a yet poorly understood mechanism. We visualized the crucial steps of the entry pathway of bovine herpesvirus 1 (BHV-1) and BHV-5 by transmission and scanning electron microscopy, employing cryotechniques that include time monitoring, ultrarapid freezing, and freeze substitution of cultured cells inoculated with virus. A key step in the entry pathway of both BHV-1 and BHV-5 is a unique fusion of the outer phospholipid layer of the viral envelope with the inner layer of the plasma membrane and vice versa resulting in “crossing” of the fused membranes and in partial insertion of the viral envelope into the plasma membrane. The fusion area is proposed to function as an axis for driving the virus particle into an invagination that is concomitantly formed close to the fusion site. The virus particle enters the cytoplasm through the opened tip of the invagination, and the viral envelope defuses from the plasma membrane. There is strong evidence that the intact virus particle is then transported to the nuclear region.